2015
DOI: 10.1103/physreva.92.012119
|View full text |Cite
|
Sign up to set email alerts
|

Weak values in continuous weak measurements of qubits

Abstract: For continuous weak measurement of qubits, we obtain exact expressions for weak values (WVs) from the post-selection restricted average of measurement outputs, by using both the quantumtrajectory-equation (QTE) and quantum Bayesian approach. The former is applicable to short-time weak measurement, while the latter can relax the measurement strength to finite. We find that even in the "very" weak limit the result can be essentially different from the one originally proposed by Aharonov, Albert and Vaidman (AAV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 65 publications
2
27
0
Order By: Relevance
“…If we compare the distributions (24) and (34), we see that the results of the previous section are reproduced in the limit → 0, as well as in the limit of T ( 2 t a ) −1 if we take σ 2 = t a /4T . The distribution (34) thus generalizes (24) to the case where the Hamiltonian dynamics is relevant.…”
Section: Sudden Jump: a Simple Considerationmentioning
confidence: 99%
See 2 more Smart Citations
“…If we compare the distributions (24) and (34), we see that the results of the previous section are reproduced in the limit → 0, as well as in the limit of T ( 2 t a ) −1 if we take σ 2 = t a /4T . The distribution (34) thus generalizes (24) to the case where the Hamiltonian dynamics is relevant.…”
Section: Sudden Jump: a Simple Considerationmentioning
confidence: 99%
“…Indeed, one can relate the above result with weak value to conform to the definition [17] if one takes into account the evolution of the quantum state during the measurement [33]. However, we need to stress that the full distribution of the outputs cannot be obtained with the traditional weak value formalism and so far has not been obtained with its extensions [22][23][24] for continuous measurement. The method outlined here does not explicitly evoke the notion of weak values and provides a more elaborated description of a realistic measurement process.…”
Section: Sudden Jump: a Simple Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we present an analysis of the weak-value-based scheme for qubit state tomography in the cQED system. In order to apply to generic parameter conditions, our study will focus on the finite strength of weak measurement [38,39]. This goes beyond the usual limit of vanishing strength, and thus results in a generalized pre-and post-selection (PPS) average, rather than the original AAV WV, as the shift of the pointer in the apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, very recent research has shown that stronger finite-strength measurement can give a better result in state tomography [40], while some efforts are devoted to developing new schemes of dispersive readout [41][42][43], which go beyond the standard approach used in the state-of-the-art experiments [28][29][30][31][32][35][36][37] and in our present work. To extract the AAV WV from the PPS average (raw signal), we propose to apply the analytic formula derived for the homodyne measurement in circuit QED [39]. By varying the phase of the local oscillator (LO), one can easily extract the complex weak value and determine the complex wavefunction by applying a simple iterative algorithm.…”
Section: Introductionmentioning
confidence: 99%